2000
DOI: 10.1063/1.372989
|View full text |Cite
|
Sign up to set email alerts
|

Charge distribution and conduction characteristics of 2-vinylpyridine-grafted polyethylenes

Abstract: This article describes electrical properties such as space charge distribution and electrical conduction characteristics of 2-vinylpyridine (VP) grafted low density polyethylenes (PE). The VP incorporated onto PE chains changes electrical properties of PE. For example, the homocharge found in virgin PE decreases with the increase of graft ratio. As a result of the nitrogen acting as an electron donor, no space charge develops at high graft ratios. It has been found that VP reduces the current density in PE. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…(1) which can be observed experimentally (Carbone et al, 2005;Laha & Krupanidhi, 2002;Suh et al, 2000), and can be derived theoretically (Coelho, 1979) ε > 0 be both independent of the position x from the electrode where the electric current flows into the dielectric sample. The flow direction of the electric current is then given by the positive direction of x.…”
Section: J~vmentioning
confidence: 97%
See 3 more Smart Citations
“…(1) which can be observed experimentally (Carbone et al, 2005;Laha & Krupanidhi, 2002;Suh et al, 2000), and can be derived theoretically (Coelho, 1979) ε > 0 be both independent of the position x from the electrode where the electric current flows into the dielectric sample. The flow direction of the electric current is then given by the positive direction of x.…”
Section: J~vmentioning
confidence: 97%
“…SCLC. Here, we have deliberately aborted the assumption of a perfectly insulating ferroelectric film, as adopted by some other schools of thought (Alpay et al, 2003;Mantese & Alpay, 2005;Okatan et al, 2010), because experimental observations of small but finite leakage currents, as well as of SCLC currents, have been widely reported in the literature for ferroelectrics and other solid dielectrics (Bouregba et al, 2003;Carbone et al, 2005;Coelho, 1979;Laha & Krupanidhi, 2002;Pope & Swemberg, 1998;Poullain et al, 2002;Suh et al, 2000) and they form a subject of their own (Pope & Swemberg, 1998). For our consideration of SCLC in compositionally graded ferroelectric films, the MottGurney law J ~ V 2 does not apply, due to the following reasons: (i) In the case of a timevarying applied voltage, there is also the presence of displacement currents so that the conduction current J , which now does not necessarily equal the total current, could be varying with position, i.e.…”
Section: Polarization Offsets In Graded Ferroelectrics and The Need Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjusting the macromolecular chain structure by grafting is an efficient modification method. Many studies have reported the effect of functional monomers grafted onto polymers on the electrical properties of materials 34–36 . It was found that the PP‐ g ‐maleic anhydride featured improved electrical breakdown strength and markedly suppressed space charge accumulation 28 .…”
Section: Introductionmentioning
confidence: 99%